TRAIL and Ceruloplasmin Inverse Correlation as a Representative Crosstalk between Inflammation and Oxidative Stress - Tisato, Veronica; Gallo, Stefania; Melloni, Elisabetta; Celeghini, Claudio; Passaro, Angelina; Zauli, Giorgio; Secchiero, Paola; Bergamini, Carlo; Trentini, Alessandro; Bonaccorsi, Gloria; Valacchi, Giuseppe; Zuliani, Giovanni; et al. (Mediators of Inflammation, 2018)
Objective. “Oxinflammation” is a recently coined term that defines the deleterious crosstalk between inflammatory and redox systemic processes, which underlie several diseases. Oxinflammation could be latently responsible for the predisposition of certain healthy individuals to disease development. The oxinflammatory pathway has been recently suggested to play a crucial role in regulating the activity of TNF-related apoptosis-inducing ligand (TRAIL), a TNF superfamily member that can mediate multiple signals in physiological and pathological processes. Therefore, we investigated the associations between TRAIL and key players of vascular redox homeostasis. Methods. We measured circulating TRAIL levels relative to praoxonas-1, lipoprotein phospholipase-A2, and ceruloplasmin levels in a cohort of healthy subjects (n=209). Results. Multivariate analysis revealed that ceruloplasmin levels were significantly inversely associated with TRAIL levels (r=−0.431, p<0.001). The observed association retained statistical significance after adjustment for additional confounding factors. After stratification for high-sensitivity C-reactive protein levels, the inverse association between TRAIL and ceruloplasmin levels remained strong and significant (r=−0.508, p<0.001, R2=0.260) only in the presence of inflammation, confirming the role of inflammation as emerged in in vitro experiments where recombinant TRAIL decreased ceruloplasmin expression levels in TNF-treated PBMC cultures. Conclusion. The results indicated that in an inflammatory milieu, TRAIL downregulates ceruloplasmin expression, highlighting a signaling axis involving TRAIL and ceruloplasmin that are linked via inflammation and providing important insights with potential clinical implications.